BIODIVERSITY OF ARTHROPOD FAUNA IN TAMIL NADU CABBAGE ECOSYSTEMS - K. SENGUTTUVAN, (The Journal of Research ANGRAU, 2023)
The experiment was conducted to evaluvate the arthropods diversity in cabbage ecosystem during 2013 to 2014. The sampling of arthropods was conducted using four different methods. The collected arthropods were sorted out, identified to the lowest possible taxon and the biodiversity indices were estimated. The class Insecta was the most common, followed by Arachnida. A total of 2866 arthropods from 8 orders and 26 families were collected from cababge ecosystem. Totally, six families of Lepidoptera were collected with the majority of individuals falling under the family Plutellidae and Pyralidae in both sprayed and unsprayed cabbage fields. Among the endopterygotes, maximum individuals were from Lepidoptera, while Hemiptera was predominant in terms of individuals of exopterygota. Among the four families of hemipterans collected, majority of the individuals were from Aphididae and Pentatomidae followed by Pseudococcidae. The biodiversity indices were worked out and at generic level varied between a minimum of 32 during the first fortnight of April to a maximum of 40 during second fortnight of June in unsprayed cabbage. In sprayed cabbage, the maximum (38)was during the first fortnight of May and the minimum (26) during the first fortnight of April. Based on ordinal level and species level analysis, the species richness was not clear in variation from the Fisher’s alpha index values. At generic level, the value was the highest in the first fortnight of May in sprayed field (10.198). The highest ordinal and familial level indices were 1.8397 in first fortnight of June and 7.8919 in second fortnight of June in sprayed cabbage.